2020
DOI: 10.1371/journal.pone.0235702
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle dysregulation in rheumatoid arthritis: Metabolic and molecular markers in a rodent model and patients

Abstract: Rheumatoid arthritis (RA) is accompanied by pain, inflammation and muscle weakness. Skeletal muscle inflammation and inactivity are independently associated with muscle insulin resistance and atrophy. Our objective was to identify early molecular and biochemical markers in muscle from a rodent model of RA relative to control and subsequently identify commonality in muscle gene expression between this model and muscle from RA patients. Pain behaviour and locomotor activity were measured in a collagen-induced ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Our results showed that the arthritic mice lost weight compared to the healthy controls. These results support earlier research indicating that chronic arthritis frequently results in weight loss due to the systemic or local activity of inflammatory cytokines such as TNF-α and IL-1β, which are produced predominantly by the monocytes and macrophages that cause muscle degeneration and loss of appetite [50,51]. Our study demonstrated that administering OL-EAE to CIA mice resulted in weight gain.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the arthritic mice lost weight compared to the healthy controls. These results support earlier research indicating that chronic arthritis frequently results in weight loss due to the systemic or local activity of inflammatory cytokines such as TNF-α and IL-1β, which are produced predominantly by the monocytes and macrophages that cause muscle degeneration and loss of appetite [50,51]. Our study demonstrated that administering OL-EAE to CIA mice resulted in weight gain.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is difficult to separate the energy-generating functions of fatty acids in the mitochondria from other roles in RA based solely on abundance measurements. Changes in fatty acid metabolism may also perpetuate extra-articular symptoms of RA, for example differential expression of enzymes involved in fatty acid metabolism were observed in skeletal muscle tissue in an arthritis model and RA patients ( 96 ).…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…This systemic inflammation can also lead to secondary sarcopenia, which appears to be primarily driven by catabolic processes. When systemic inflammation persists and is associated with anorexia, asthenia, and/or physical inactivity, additional muscle loss pathways are activated, altering the balance of muscle tissue remodelling, and may activate different intracellular proteolysis pathways [3][4][5].…”
Section: Introductionmentioning
confidence: 99%